Challenges in Managing Patients with Hereditary Cancer at Gynecological Services - Mako Ueda; Hiroshi Tsubamoto; Mina Kashima-Morii; Yoshitaka Torii; Mariko Kamihigashi; Yu Wakimoto; Nami Nakagomi; Tomoko Hashimoto-Tamaoki; Hideaki Sawai; Hiroaki Shibahara (Obstetrics and Gynecology International)
Aim. To reveal current problems and challenges faced by our gynecologic services department in managing patients with hereditary cancers. Methods. We collected clinical data of patients with hereditary cancers, identified via genetic testing (or clinically diagnosed in cases of Cowden syndrome or Peutz–Jeghers syndrome), and treated in our gynecological department from 2012 to 2018. Results. Fifteen patients had hereditary breast and ovarian cancer (HBOC), 6 had Lynch syndrome, 2 had Cowden syndrome, and 2 had Peutz–Jeghers syndrome. Five patients diagnosed with HBOC were younger than 40 years at diagnosis. Risk-reducing salpingo-oophorectomy (RRSO) was performed on 1 patient with a BRCA1 mutation at age 38 years. Seven patients overall underwent RRSO, and none had malignancies on pathological examinations. Peritoneal washing cytology (PWC) was suspicious for malignancy in one patient; however, subsequent PWC at 6 months after RRSO was negative. A patient with endometrial cancer and Lynch syndrome and a patient with atypical endometrial hyperplasia (AEH) and Cowden syndrome strongly desired fertility preservation. They achieved remission after medroxyprogesterone acetate treatment and multiple dilations and curettages, respectively. One patient with Lynch syndrome developed AEH after 11 years of surveillance. Laparotomy revealed adjacent low-grade and high-grade serous ovarian cancer with positive ascites cytology. She had no recurrence during 7-year follow-up after laparotomy. Conclusion. Managing patients with hereditary cancer, positive or false-positive ascites cytology discovered during RRSO, and desired preservation of fertility is highly challenging.